The social significance and appeal of opera theatre (17th–19th centuries) - Markiewicz, Grzegorz (A mosaic city: The culture-oriented description, 2023)
The theatre was not only an artistic institution, a focus for the most important achievements and trends in literature, music, visual arts and dance, but also a very important institution of social life, a space where one could show off, flirt, do business; in a word, the theatre was the place to visit. Opera was meant to enchant, dazzle and seduce. An opera performance was an extremely expensive investment. Singers, choristers, dancers and musicians had to be paid. Investments had to be made in machinery and special effects. The basic genres were classical opera and comic opera. These took different forms, particularly divergent in Italy and France.